Phenotype and Genotype Analyses of Ornithine Transcarbamylase Deficiency in Taiwanese - 黃淵德(Yuan-Td Huang); 簡穎秀(Yin-Hsiu Chien); 葉慧英(Hui-Ying Yeh); 林秀娟(Shio-Jean Lin); 呂立(Frank Li Lu); 周西平(Shi-Ping Chou); 林京美(Jing-Meei Lin); 蔣書娟(Shu-Chuan Chiang); 胡務亮(Wuh-Liang Hwu) (Journal of the Formosan Medical Association, 2003)
Ornithine transcarbamylase (OTC) deficiency is the most common inherited urea cycle disorder. It is an X-linked semidominant disease with variable severity affecting both males and females. The characteristics and course have not been assessed in Taiwanese. This study analyzed the phenotype and genotype of OTC deficiency in Taiwanese. During the period from January 1993 to December 2001 inclusive, 8 patients had the diagnosis of OTC deficiency by the criteria of hyperammonemia, hypocitrullinemia, and orotic aciduria. All 10 exons of the OTC gene were analyzed for mutations. Among the 8 cases, 3 belonged to the early-onset group (initial symptoms before or equal to age 28 days) and 5 belonged to the late-onset group (median onset age, 18 months; range, 8 months to 52 years). One case in the former group, and 4 cases in the latter group survived (mean survival, 8.2 years; range, 3 to 16 years). The average time between initial symptoms and diagnosis was 60 months in the late-onset group. Analysis of the OTC genes detected 5 different mutations in 5 patients, including 3 novel mutations: 42delT, 652G>A, and 791C>A. IQ tests, conducted in 3 patients, revealed low scores (mean, 53; range, 40 to 72). Both early-onset and late-onset cases of OTC deficiency were identified in Taiwanese. The diagnosis was delayed in these patients, and their outcomes were poor. All mutations detected were different and most of them have not been reported in other populations, which may explain the variability of phenotypes in Taiwanese patients.